Functional Probes: Flexible Fiber Probe for Efficient Neural Stimulation and Detection (Adv. Sci. 15/2020). Issue 15 (5th August 2020) - Du, Minghui; Huang, Lu; Zheng, Jiajun; Xi, Yue; Dai, Yi; Zhang, Weida; Yan, Wei; Tao, Guangming; Qiu, Jianrong; So, Kwok‐Fai; Ren, Chaoran; Zhou, Shifeng
Abstract : In article number 2001410, Chaoran Ren, Shifeng Zhou, and co‐workers report a category of tiny fiber probes with metal electrodes regularly embedded inside the double‐clad biocompatible polymer fiber. This arrangement enables a probe with excellent mechanical properties, high transmission, and low impedance, which can realize long‐term simultaneous optical stimulation and neural recording at the single‐cell level in behaving mice with high signal‐to‐noise ratio.